Giovanni Battista De Vecchis and the theory of melodic accent from Zarlino to Zingarelli - Baragwanath, Nicholas (Oxford University Press, 2014)
This article investigates Niccolo' Zingarelli’s method of text-setting, as documented in Giovanni Battista De Vecchis’s Compendio of Neapolitan teachings (1850). It contextualizes De Vecchis’s instructions by tracing the genealogy of the concept of ‘accent’ as understood by early nineteenth-century composers through successive reinterpretations of an Italian theory of qualitative rhythmopoeia established in the sixteenth century, which accounted for rhythm, metre, and pitch through a threefold division of accent. The article explores its origins, its treatment by Zarlino, its significance in writings by nineteenth-century Italian musicians, and the confusing alternative terminology circulated by Rousseau (1768).The Neapolitan doctrine of text-setting presents a historical example of a ‘drastic’ approach to conceptualizing music, recognizing the priority of unruly human performance over abstract rationalization, in contrast to the ‘gnostic’ theories of Sulzer and Koch, with their emphasis on notated melodies and their subordination of rhythm (as spoken, sung, or played) to quantifiable metric grids.